Static Behavior of Circular Section CFRP Concrete-Filled Steel Tubes Under Compressive–Torsional Load - Wang, Qing-li; Zhao, Jie; Peng, Kuan (Frontiers in Materials, 2022)
Abstract: In order to study the compressive torsional behavior of concrete filled CFRP steel tubular (CF-CFRP-ST), the static test of 8 circular section CF-CFRP-ST compression torsional specimens were carried out. The characteristics of torque-angle (T-) curve and shear stress shear-strain (-) curve, failure mode, cooperative work between steel tube and CFRP and cross-section assumption were studied. The T- curve, - curve and failure mode of the specimen are simulated by ABAQUS. Based on the above research and the stress distribution of each component material are analyzed. The effects of transverse CFRP layers, material strength, steel ratio and axial compression ratio on the static performance of members are discussed. Based on the performance analysis, the bearing capacity equation of CF-CFRP-ST compression-torsional members is proposed.